2018
DOI: 10.3928/1081597x-20180108-01
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of Tunnel Depth for Intrastromal Corneal Ring Segments Implantation Between Manual and Femtosecond Laser Techniques

Abstract: ICRS implantation assisted by a femtosecond laser provides a more precise procedure considering dissection depth when compared with the manual dissection technique. Such an advantage may provide more predictable clinical results and safer procedures with the femtosecond laser. [J Refract Surg. 2018;34(3):188-194.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 21 publications
(28 reference statements)
1
27
0
1
Order By: Relevance
“…A recent study reported a higher accuracy and predictability of femtosecond laser for the creation of intrastromal tunnel compared to the manual technique. 7 Hence, it seems appropriate to analyse if those results have impact on the visual and refractive outcomes of the ICRS implantation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported a higher accuracy and predictability of femtosecond laser for the creation of intrastromal tunnel compared to the manual technique. 7 Hence, it seems appropriate to analyse if those results have impact on the visual and refractive outcomes of the ICRS implantation.…”
Section: Introductionmentioning
confidence: 99%
“…19 Only Kouassi et al 35 found in a prospective comparative study that both mechanical and femtosecond laser-assisted Intacs implantations showed a more superficial ring segment placement than predicted, with no statistically significant difference between techniques. Differences in the sample evaluated and in the clinical and surgical protocols followed in this study and in the study of Monteiro et al, 26 and by our research group in the current series may account for this discrepancy.…”
Section: Discussionmentioning
confidence: 55%
“…This is consistent with the results of previous studies showing a high level of accuracy in the lamellar dissection achieved with the femtosecond laser. [26][27][28] Monteiro et al 26 found in a multicenter comparative study that ICRS implantation assisted by a femtosecond laser was a more precise procedure in terms of dissection depth when compared with the manual dissection technique. Naftali and Jabaly-Habib 29 found that the depth of implantation of ICRS measured by OCT was less than expected when the mechanical technique was used for ring segment implantation.…”
Section: Discussionmentioning
confidence: 99%
“…OCT can help to accurately determine the thickness of the cornea at the site of ring placement pre‐, intra‐ and post‐operatively (Figure ) . Pre‐operatively, OCT can quantitatively and qualitatively evaluate the corneal stroma before implantation to ensure there is adequate depth for ring placement; intra‐operatively, OCT can be used to assess manual or femtosecond laser created tunnels before implantation of the intrastromal ring . Post‐operatively, OCT can be used to monitor segment migration and depth so that complications can be more readily anticipated …”
Section: Hydropsmentioning
confidence: 99%